2020
DOI: 10.2147/ott.s281962
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-519d and miR-328-3p Combinatorially Suppress Breast Cancer Progression</p>

Abstract: Background MiR-519d and miR-328-3p had tumor-regulatory properties in different cancers, but their combinatorial effects and potential common target in breast cancer had not been fully reported. This research targeted to study the underlying mechanism of how miR-519d and miR-328-3p cooperatively suppressed breast cancer. Methods MiR-519d and miR-328-3p expressions in breast cancer tissues and cells were assessed and Ki-67 expression was also checked. DLR assay was execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In addition, the miR-328 decreased chemoresistance by targeting several genes involved in the ABC transporter, such as ABCG2 also known as breast cancer resistance protein BCRP, ABCD3 [ 61 , 62 ]. Suggested as a novel biomarker for the diagnosis and as a promising strategy for therapeutic manipulation, miR-328-3p combined with miR-519d suppressed breast cancer progression by targeting Ki67 [ 63 ]. Reported as a potential non-invasive poor prognosis biomarker for AML patients, deeper investigation of the main functions of the miR-328-3p in the AML stem cell chemoresistance capacity, which combined with another miRNA, might downregulate common target genes, which code survival signaling proteins, could eventually be a promising strategy to overcome AML relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the miR-328 decreased chemoresistance by targeting several genes involved in the ABC transporter, such as ABCG2 also known as breast cancer resistance protein BCRP, ABCD3 [ 61 , 62 ]. Suggested as a novel biomarker for the diagnosis and as a promising strategy for therapeutic manipulation, miR-328-3p combined with miR-519d suppressed breast cancer progression by targeting Ki67 [ 63 ]. Reported as a potential non-invasive poor prognosis biomarker for AML patients, deeper investigation of the main functions of the miR-328-3p in the AML stem cell chemoresistance capacity, which combined with another miRNA, might downregulate common target genes, which code survival signaling proteins, could eventually be a promising strategy to overcome AML relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, it has been indicated that microRNAs (miRNAs) are downregulated in many types of cancers (13,14). This study is the initial attempt to explore the potential link between miR-143 gene polymorphisms (rs4705342) and oral squamous cell carcinoma (OSCC) susceptibility in an Iranian community.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study reported that inhibition of miR-328-3p impairs ovarian CSCs function, a finding that is inconsistent with our results [ 33 ]. For this reason, we examined relevant literature and found that miR-328-3p has different roles in different human cancers [ 8 10 , 12 , 32 , 33 ], indicating that the function of miR-328-3p could be tissue and tumor specific.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that miR-328-3p can downregulate ABCG2 in some BC cell lines, and plays a role in drug resistance [ 11 ]. However, other reports have indicated that miR-328-3p can counteract the BC malignant phenotype [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%